Hadrah Sebagai Media Dakwah Dalam Meningkatkan Perilaku Keagamaan Pemuda Majlis Ta’lim Arafah Bojonggede Bogor - Farhat Sauri, Ahmad; Masruroh, Sayidah Afyatul (Menara Tebuireng, 2024)
Abstract— This study explores the impact of hadrah as a means of Islamic propagation in enhancing the religious behavior of youth in Majlis Ta'lim Arafah Bojonggede, Bogor. Majlis Ta'lim Arafah Bojonggede is a regular activity of the local community, often conducted more frequently than special gatherings for Islamic students, with the main events usually held on Friday evenings and during major Islamic holidays. The implementation of hadrah as a means of Islamic propagation involves several concrete steps, such as integration into events, training and practice, Islamic content in hadrah, empowerment of youth, and evaluation. The impact of hadrah is evident in the increased enthusiasm for Islamic propagation, the positive psychological reception of messages, and its significance in shaping Islamic behavior. In the context of Edward L. Deci's theory of intrinsic and extrinsic motivation, it is found that intrinsic motivation, stemming from internal satisfaction, and extrinsic motivation, stemming from external factors, mutually influence each other in enhancing engagement and Islamic behavior. In conclusion, hadrah as a means of Islamic propagation can significantly contribute to enhancing the religious behavior of youth, with intrinsic and extrinsic motivation playing a crucial role in this process. Keywords: Hadrah, Islamic propagation, Religious behavior, Intrinsic motivation, Extrinsic motivation